Design and experiment of low-damage and high-cleanliness segmented combined peeling roller for maize peeling device - Li, Zhenye; Fu, Jun; Xue, Zhao; Fu, Qiankun; Luo, Xiwen (International Journal of Agricultural and Biological Engineering, 2026)
Aiming at the key technical bottleneck that the high bract stripping rate and low grain damage rate are mutually restricted during the peeling process of maize ear harvesters, a segmented combined peeling roller was designed to achieve the operational goal of “low damage and high cleanliness”. By establishing the contact mechanical model between the convex ribs and the maize ear and analyzing the dynamic process of maize ear peeling, the arc convex rib-groove structure and the three-section combined configuration were determined, which realized graded adaptation and low-damage, high-cleanliness operation in the peeling process. Friction characteristic tests, simulation tests, orthogonal optimization tests, and field verification tests were carried out. The results showed that the rolling friction coefficient and contact stress between the segmented combined peeling roller and the maize ear decreased sequentially from the front section to the rear section. Using the Box-Behnken response surface method to optimize the operating parameters, the optimal parameter combination was obtained: the peeling roller speed was 353 r/min, the pressing wheel speed was 82 r/min, and the distance between the peeling roller and pressing wheel was 31 mm. Compared with the conventional fish-scale spiral peeling roller, the bract stripping rate of the designed segmented combined peeling roller was increased by 10.89%, while the grain shedding rate and grain breaking rate were reduced by 68.93% and 63.51%, respectively. This study provides theoretical support and engineering reference for the optimal design of the low-damage and high-cleanliness maize peeling devices. Key words: maize; mechanical peeling; peeling roller; low damage and high cleanliness; segmented combined DOI: 10.25165/j.ijabe.20261904.9836 Citation: Li Z Y, Fu J, Xue Z, Fu Q K, Luo X W. Design and experiment of low-damage and high-cleanliness segmentedcombined peeling roller for maize peeling device. Int J Agric & Biol Eng, 2026; 19(4): 88–97.